Modelling the mechanical response of elastomers: the roles of the network, the filler and the deformation history - Annarasa, Vinotharan (2021)
The mechanical response of elastomers is influenced by a large range of factors including the elastomeric network, the deformation history (or Mullins effect) and the type and content of filler. The aim of this work is to develop modelling frameworks and models to capture the influences of these factors in selected elastomer systems. Several experimental studies were conducted to aid in the development and validation of the models.